Mean Amplitudes of Vibration of the trans-IO2F52- Anion - Barán, Enrique José (2004)
The mean amplitudes of vibration of the trans-IO2F52--anion have been calculated from recently reported spectroscopic and structural data between 0 and 1000 K. Bond peculiarities are discussed in comparison with those of related species.